Inkar Sunah: Asal Usul dan Perkembangan Pemikiran Inkar Sunah di Dunia Islam - Zarkasih Zarkasih (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2012)
Inkar al-Sunna is a teaching that arises in minority of Muslims who reject the legal basis of Islam ‘sunnah sahihah’ either partly or wholly without an acceptable reason by Muslim scholars or ulama. The initial symptoms of this thoughts was already there from an early age, but as a growing understanding that had happened since the end of the second century of Hijra or seventh century BC, i.e. at the time of al-Shafi'i (d. 204 H). Then, along with the colonization of Western countries to the Islamic world, it reappeared in modern times in many Islamic countries such as Egypt, India, Malaysia, and Indonesia. Because of the persistence and struggle of Muslim scholars or ulama, inkar sunnah movement successfully minimized so that Islam can be maintained from the defilement thoughts